Low Circulating Monocytes Is in Parallel With Lymphopenia Which Predicts Poor Outcome in Anti-melanoma Differentiation-Associated Gene 5 Antibody-Positive Dermatomyositis-Associated Interstitial Lung Disease - Lv, Xia; Jin, Yuyang; Zhang, Danting; Li, Yixuan; Fu, Yakai; Wang, Suli; Ye, Yan; Wu, Wanlong; Ye, Shuang; Yan, Bing; Chen, Xiaoxiang (Frontiers in Medicine, 2022)
Anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive dermatomyositis (DM)-associated interstitial lung disease (ILD) may progress rapidly and lead to high mortality within 6 or 12 months. Except for reported prognostic factors, simple but powerful prognostic biomarkers are still in need in practice. In this study, we focused on circulating monocyte and lymphocyte counts and their variation tendency in the early stage of ILD. A total of 351 patients from two inception anti-MDA5 antibody-positive cohorts were included in this study, with various treatment choices. Lymphocyte count remained lower in the first month after admission in the non-survivor patients. Although baseline monocyte count showed no significant differences, average monocyte count in the following four weeks was also lower in the non-survivor group. Based on the c-index and analysis by ‘survminer’ R package in the discovery cohort, we chose 0.24x109/L as cut-off value for Mono W0-2, 0.61x109/L as cut-off value for Lymph W0-2, and 0.78x109/L as cut-off value for PBMC W0-2, to predict the 6-month all-cause mortality. Kaplan-Meier survival curves and adjusted hazard ratio with age, gender, and the number of immunosuppressants used all validated that patients with lower average monocyte count, lower average lymphocyte count, or lower average PBMC count in the first two weeks after admission had higher 6-month death risk, no matter in the validation cohort or in the pooled data. Furthermore, flow cytometry figured out that non-classical monocytes in the anti-MDA5 antibody-positive DM patients were significantly lower than healthy controls and DM patients without anti-MDA5 antibodies. In conclusion, our study elucidated the predictive value of monocyte and lymphocyte counts in the early stage and may help rheumatologists to understand the possible pathogenesis of this challenging disease.